2009
DOI: 10.1021/cr800187m
|View full text |Cite
|
Sign up to set email alerts
|

From Vinylidene Fluoride (VDF) to the Applications of VDF-Containing Polymers and Copolymers: Recent Developments and Future Trends

Abstract: Dedicated to Professor Bernard Boutevin on honor of his 60 th birthday CONTENTS 3.3.6. Poly(VDF-co-Comonomer) Copolymers Controlled via Xanthates 3.3.7. Conclusion 4. WELL-DEFINED COPOLYMERS BASED ON VINYLIDENE FLUORIDE 4.1. Fluorinated Block Copolymers Based on VDF 4.1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
715
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 700 publications
(736 citation statements)
references
References 377 publications
(707 reference statements)
15
715
1
5
Order By: Relevance
“…However, peaks derived from reverse head-to-head linkages are usually observed in VDF-based telomers, 21 oligomers 23 and copolymers. 2,3,24 Nevertheless, in the iodine transfer polymerization of VDF in the presence of C 6 F 13 I or C 6 F 13 CH 2 CF 2 I, reverse head-to-head additions were not observed. 13,14 The 1 H NMR spectrum of the telomer (Figure 2, lower spectrum) was in agreement with the results of 19 F NMR spectroscopy.…”
Section: Piezoelectric Properties Of Vdf Telomers N Durand Et Almentioning
confidence: 95%
See 3 more Smart Citations
“…However, peaks derived from reverse head-to-head linkages are usually observed in VDF-based telomers, 21 oligomers 23 and copolymers. 2,3,24 Nevertheless, in the iodine transfer polymerization of VDF in the presence of C 6 F 13 I or C 6 F 13 CH 2 CF 2 I, reverse head-to-head additions were not observed. 13,14 The 1 H NMR spectrum of the telomer (Figure 2, lower spectrum) was in agreement with the results of 19 F NMR spectroscopy.…”
Section: Piezoelectric Properties Of Vdf Telomers N Durand Et Almentioning
confidence: 95%
“…Among organic ferroelectrics, CF 3 (VDF) 17 I possesses a relatively high remanent polarization. 9 Furthermore, previous experiments on CF 3 (VDF) 13.4 C 2 H 5 revealed that the piezoelectric coefficient of VDF telomers was greater than that of oligo(VDF-co-TrFE) copolymers, and a thinner and more uniform film could be obtained. 6,7 The objective of this study was to design various VDF-based telomers, such as C n F 2n+1 (VDF) p -(C 2 H 4 ) x -X (where n¼4 or 6; p¼6-23; x¼0, 1 and X¼H or I), and to alter the crystallinity, ferroelectric and piezoelectrical properties by controlling the number of VDF units and end groups.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although hydrophobic modification of existing membranes or polymers is widely applied to further improve the properties and performance of hydrophobic membranes, seeking or synthesizing a substituted polymer for hydrophobic membranes is another effective way to obtain an ideal membrane (Kang and Cao, 2014). Recently, PVDF-based copolymers like poly (vinylidene fluoride-co-tetrafluoroethylene) (PVDF-TFE), poly (vinylidene fluoride-co-trifluoroethylene) (PVDF-TrFE), poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) and some kinds of PVDF-based graft copolymers have been applied in hydrophobic membrane preparation studies (Ameduri, 2009;Cui et al, 2014). These copolymers possess higher hydrophobicity due to their high fluorine content, and have attracted considerable attention as an alternative choice for hydrophobic membrane preparation (Feng et al, 2004(Feng et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%